2011
DOI: 10.1002/hep.24298
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in interleukin 28B with respect to vertical transmission of hepatitis C virus and spontaneous clearance in HCV‐infected children

Abstract: The vertical transmission of hepatitis C virus (HCV-VT) is a major route of HCV infection in children, but the risk factors remain incompletely understood. This study analyzed the role of interleukin 28B (IL28B) in HCV-VT and in the spontaneous clearance of HCV among infected infants. Between 1991 and 2009, 145 mothers were recruited for this study: 100 were HCV-RNA1ve / human immunodeficiency virus negative (HIV2ve), with 128 children, and 33 were HCV-RNA2ve/HCV antibody1ve, with 43 children. The infants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 28 publications
8
75
0
1
Order By: Relevance
“…They found a tendency (p=0.0813) towards a higher frequency of allele T in the group of patients according to the controls, but no significant difference in the genotypic frequency (p=0.1865) was found between the two groups. In other studies, the CC genotype played a major role in viral clearance caused by treatment (34,35). In our study, 44.6% of the cases in the control group were CC, 46.7% of the cases were CT, and 8.7% were TT.…”
Section: Discussionsupporting
confidence: 55%
“…They found a tendency (p=0.0813) towards a higher frequency of allele T in the group of patients according to the controls, but no significant difference in the genotypic frequency (p=0.1865) was found between the two groups. In other studies, the CC genotype played a major role in viral clearance caused by treatment (34,35). In our study, 44.6% of the cases in the control group were CC, 46.7% of the cases were CT, and 8.7% were TT.…”
Section: Discussionsupporting
confidence: 55%
“…In our six patients, the combination of the longitudinal course of LFTs plus HCV gene copy number appeared to aid in predicting the chance of viral resolution. As mentioned in our paper, we concur that other features of HCV infection, such as viral genotype and IL28B polymorphisms, contribute to viral resolution in children [1,3,4]. Therefore, information on IL28B polymorphisms in our patients would have been interesting.…”
supporting
confidence: 84%
“…Besides, several global stud ies have revealed that the C/C genotype is the major player in drug-induced viral clearance, while both the C/T and T/T genotypes have a poor association with clearance rates (Liao et al, 2011;Ruiz-Extremera et al, 2011). Similarly, host factors control tolerance to chronic HBV infection and can fluctuate over time with increased risk of progression to cirrhosis and particularly HCC (Eksteen, 2011).…”
Section: Discussionmentioning
confidence: 99%